Peningkatan Daya Saing UMKM WMie Melalui Pemasaran Digital dan Penerapan Pencatatan Keuangan Sistematis dengan Aplikasi SIAPIK - Erlynda Yuniarti Kasim; Cynthia Riyanti Martaba (Jurnal Dharma Bhakti Ekuitas, 2025)
This community service program was carried out with the aim of enhancing the competitiveness of WMie MSMEs by strengthening digital marketing and structuring financial management, which had previously been unorganized. WMie MSMEs, operating in the culinary sector and located in a local area, faced several challenges, particularly in expanding market reach and managing finances as well as raw material inventory efficiently. The program was designed to provide solutions through the introduction of digital marketing strategies using social media and the implementation of the SIAPIK financial recording application. The methods applied included intensive digital marketing training, SIAPIK application implementation, and continuous assistance in inventory management and financial recording. The results of the program showed significant impacts, as WMie successfully increased market exposure through social media engagement, particularly with a 30% growth in Instagram followers and thousands of views on TikTok content. From the financial perspective, the implementation of the SIAPIK application resulted in more transparent, organized, and efficient financial records. Additionally, this system reduced raw material waste by up to 25%, thereby improving operational effectiveness. Overall, this community service activity brought positive changes by strengthening the competitiveness of WMie MSMEs in wider markets while opening opportunities for expansion through franchise collaboration. Thus, the use of digital technology has proven to make a major contribution in supporting efficiency, business sustainability, and MSME development in today’s competitive era. Keywords: digital marketing, systematic financial recording, inventory management, SIAPIK Abstrak Pengabdian kepada masyarakat ini dilaksanakan dengan tujuan untuk meningkatkan daya saing UMKM WMie melalui penguatan pemasaran digital dan penataan manajemen keuangan yang selama ini belum terstruktur. UMKM WMie, yang bergerak di bidang kuliner dan berlokasi di kawasan lokal, menghadapi sejumlah kendala, terutama dalam memperluas jangkauan pasar serta mengelola keuangan dan persediaan bahan baku secara efisien. Program ini dirancang untuk memberikan solusi melalui pengenalan strategi pemasaran digital berbasis media sosial dan penerapan aplikasi pencatatan keuangan SIAPIK. Metode yang digunakan meliputi pelatihan intensif pemasaran digital, implementasi aplikasi SIAPIK, serta pendampingan berkelanjutan dalam manajemen stok dan pencatatan transaksi. Hasil pelaksanaan kegiatan menunjukkan dampak signifikan, di mana UMKM WMie berhasil meningkatkan eksposur pasar melalui peningkatan pengikut media sosial, khususnya Instagram yang naik sebesar 30%, serta capaian jumlah tayangan konten di TikTok yang mencapai ribuan. Dari sisi manajemen keuangan, penerapan aplikasi SIAPIK menghasilkan pencatatan yang lebih transparan, rapi, dan efisien. Selain itu, sistem ini juga mampu menekan pemborosan stok bahan baku hingga 25%, sehingga meningkatkan efektivitas operasional. Secara keseluruhan, kegiatan pengabdian ini membawa perubahan positif dengan memperkuat daya saing UMKM WMie di pasar yang lebih luas, sekaligus membuka peluang ekspansi melalui pola kerjasama waralaba. Dengan demikian, penggunaan teknologi digital terbukti memberikan kontribusi besar dalam mendukung efisiensi, keberlanjutan usaha, serta pengembangan UMKM di era persaingan modern. Kata kunci: pemasaran digital, pencatatan keuangan sistematis, manajemen stok barang, SIAPIK